Jawabanmu

2014-08-29T17:46:47+07:00
3 b)= \frac{15 \sqrt{2} +3 \sqrt{7} -10 \sqrt{2} }{4 \sqrt{5} }  \frac{4 \sqrt{5} }{4 \sqrt{5} }
= \frac{ 60\sqrt{10}+12 \sqrt{35}-40 \sqrt{10}   }{80}
= \frac{ 30\sqrt{10} +12 \sqrt{35} }{80} = \sqrt{10} +3 \sqrt{35}
   c) \frac{( \sqrt{2} -1)(3)-( \sqrt{2}+1)(2) }{2-1} = \frac{3 \sqrt{2}-3-(2 \sqrt{2}+2)  }{1}
=3 \sqrt{2}-3-2 \sqrt{2}  -2= \sqrt{2} -5
4. \frac{ \sqrt{2}- \sqrt{3}  }{ \sqrt{2} + \sqrt{3} }  \frac{ \sqrt{2}- \sqrt{3}  }{\sqrt{2}- \sqrt{3}}
= \frac{2-2 \sqrt{6}+3 }{2-3} = \frac{-1-2 \sqrt{6} }{-1} =1+2 \sqrt{6}
a=1
b=2